2021
DOI: 10.3390/en15010014
|View full text |Cite
|
Sign up to set email alerts
|

GIS and Remote Sensing for Renewable Energy Assessment and Maps

Abstract: Geographic Information Systems (GIS) and Remote Sensing (RS) techniques are of great interest for the renewable energy field [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…To enhance the performance of models, several researchers have focused on maximizing their integration. Integrating GIS software and BIM models can save time and allow for more precise monitoring of construction and post-construction processes [70,71]. Numerous studies have demonstrated the successful utilization of GIS software and BIM model integration for developing and visualizing a range of functions [72].…”
Section: Gis and Bim Integrationmentioning
confidence: 99%
“…To enhance the performance of models, several researchers have focused on maximizing their integration. Integrating GIS software and BIM models can save time and allow for more precise monitoring of construction and post-construction processes [70,71]. Numerous studies have demonstrated the successful utilization of GIS software and BIM model integration for developing and visualizing a range of functions [72].…”
Section: Gis and Bim Integrationmentioning
confidence: 99%